Influencia de las estrategias metodológicas en el rendimiento escolar de los estudiantes del cuarto año de educación básica de la Unidad Educativa Ecuador Parroquia La Unión, Cantón Babahoyo, Provincia de Los Ríos - Ramirez Pacheco, Katherine del Carmen (2020)
This degree work called INFLUENCE OF METHODOLOGICAL STRATEGIES IN THE SCHOOL PERFORMANCE OF THE STUDENTS OF THE FOURTH YEAR OF BASIC EDUCATION OF THE EDUCATIONAL UNIT ECUADOR PARROQUIA LA UNIÓN, CANTÓN BABAHOYO, PROVINCE OF THE RIVERS has the specific purpose of determining application of methodological strategies to improve school performance. Through direct observation and instruments to collect data, it was detected that the problem that gave rise to the research was the low school performance in the students due to the incorrect application of the methodological strategies by the Teacher. Survey guides were designed for students and teachers who contributed to our research achievement. This research is based on the importance of the design and use of methodological strategies in the educational field. It is not enough to know the interiors of the subjects: to master them, and to know them; they must be sent to the student in a way that produces in him a desire for research. For this, it is necessary for the teacher to use the methodological strategies that will help him in the educational objective. Through the execution of this work we have managed to obtain excellent results, through the use of the correct application of methodological strategies, being these fundamental parts that the Teacher must use with his students so that the new knowledge is transmitted in the correct way.